PRODUKSI EPIGALLOCATECHIN GALLATE PADA KULTUR IN VITRO KALUS CAMELLIA SINENSIS SEBAGAI KANDIDAT PANGAN FUNGSIONAL (Jurnal Teknologi Pangan, 2013)
Epigallocatechin gallate (EGCG)  were  secondary metabolite in  tea  (Camellia sinenis)  as  anti  obecity dan  degenerative  syndrom.  EGCG  in  tea  act  as  bioactive  by hydroxyl group and galoil that could act as functional food substitute. Problem to find epigallocatechin gallate from tea were season dependent, need a large area, and low productivity.  By  these  mean epigallocatechin  gallate  production  by  in  vitro  culture. These technique could overcaming all that problem above. General purpose of these research  were  to  find invitro  EGCG  production technique.  Method  to  gain  these purpose were : (1)  Callus induction by explant sprout tea leaves in media  with many variance  grown  culture (2)  Sub  culture  callus  by  using  same  media  in  induction method  (3) qualitative  analisys EGCG  callus compound. Result  of  these  research; callus  hand retention  time  (tR)  on  High  Performance  Liquid  Chromatography  for  6 minutes, same as EGCG standart. EGCG had potential as aditive functional food and baverage  that had astringent or bitter tasteKey words : Epigallocatechin gallate,  HPLC, retention time, Camellia sinensis